2022
DOI: 10.3390/diagnostics12010226
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HE4, CA125, ROMA and CPH-I for Preoperative Assessment of Adnexal Tumors

Abstract: (1) OBJECTIVE: To assess the performance of CA125, HE4, ROMA index and CPH-I index to preoperatively identify epithelial ovarian cancer (EOC) or metastatic cancer in the ovary (MCO). (2) METHODS: single center retrospective study, including women with a diagnosis of adnexal mass. We obtained the AUC, sensitivity, specificity and predictive values were of HE4, CA125, ROMA and CPH-I for the diagnosis of EOC and MCO. Subgroup analysis for women harboring adnexal masses with inconclusive diagnosis of malignancy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Accurate biomarkers have been demonstrated to greatly improve the effectiveness of treatment and, thus, patient's quality of life. The risk of ovarian malignancy algorithm (ROMA) comprising CA-125, HE-4, and menopausal status was investigated in a variety of clinical studies [5,16,17], but has not yet found its way into standard clinical use. Still, meta-analyses showed its superiority compared to single markers, such as CA-125 or HE-4 alone [18].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate biomarkers have been demonstrated to greatly improve the effectiveness of treatment and, thus, patient's quality of life. The risk of ovarian malignancy algorithm (ROMA) comprising CA-125, HE-4, and menopausal status was investigated in a variety of clinical studies [5,16,17], but has not yet found its way into standard clinical use. Still, meta-analyses showed its superiority compared to single markers, such as CA-125 or HE-4 alone [18].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent validation study of the Copenhagen Index illustrated that CPH-I (AUC 0.92; 95% CI: 0.85–0.98) was able to outperform a modified ROMA ® index (AUC 0.54; 95% CI: 0.38–0.69), but was also comparable to a biomarker panel of six serum proteins (AUC 0.90; 95% CI: 0.82–0.97) [ 70 ]. Carreras-Dieguez et al also assessed the preoperative performance of CPH-I and ROMA ® in comparison to the markers HE4 and CA125 [ 71 ]. They reported that in postmenopausal women, and women with stage I lesions, CPH-I (AUC 0.955, AUC 0.901, respectively) and ROMA ® (AUC 0.953, AUC 0.909, respectively) outperformed single markers HE4 (AUC 0.905, AUC 0.856, respectively) and CA125 (AUC 0.933, AUC 0.810, respectively) [ 71 ].…”
Section: Preoperative Diagnosticsmentioning
confidence: 99%
“…Carreras-Dieguez et al also assessed the preoperative performance of CPH-I and ROMA ® in comparison to the markers HE4 and CA125 [ 71 ]. They reported that in postmenopausal women, and women with stage I lesions, CPH-I (AUC 0.955, AUC 0.901, respectively) and ROMA ® (AUC 0.953, AUC 0.909, respectively) outperformed single markers HE4 (AUC 0.905, AUC 0.856, respectively) and CA125 (AUC 0.933, AUC 0.810, respectively) [ 71 ]. While the specificity of CPH-I is generally lower than the other algorithms, it can be contended that the test has considerable advantages over other methods since it is independent of menopausal status and TVU imaging, and could thus be employed in places where access to sonography is limited.…”
Section: Preoperative Diagnosticsmentioning
confidence: 99%
“…Circulating CA125 levels increase with tumor burden, but—conversely—they do not exceed the usual cutoff of 35 U/mL at 50% of early OC [ 15 ]. The sensitivity of CA125 has been reported at 0.78–0.86, the specificity at 0.57–0.82, the positive predictive value (PPV) at 0.50–0.68 and the negative predictive value (NPV) at 0.9–0.95 [ 11 , 12 , 16 , 17 , 18 , 19 ]. Amongst a further 200 investigated biomarkers, the cancer antigens CA 72.4, CA 15.3, CA 19.9 and HE4 have been considered the most informative for the evaluation of adnexal mass [ 4 , 13 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst a further 200 investigated biomarkers, the cancer antigens CA 72.4, CA 15.3, CA 19.9 and HE4 have been considered the most informative for the evaluation of adnexal mass [ 4 , 13 , 20 ]. HE 4 received particular attention as initial studies indicated it had better specificity (0.78–0.94) with sensitivity (0.75–0.86), PPV (0.62–0.63) and NPV (0.87–0.96) being comparable to those of CA125 [ 17 , 18 ]. In 2009, a Risk of Ovarian Malignancy Algorithm (ROMA) including CA125, HE4 and menopausal status was proposed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%